Dynamic power management by reinforcement learning - Hossain, Safayet; Ibn-Ismail, Muhammad Adnan (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.